2021
DOI: 10.34172/jpe.2021.04
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of COVID-19 by CD24FC; a mini-review to the current knowledge

Abstract: The severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) is already known for its respiratory infection, but it involved more organs such as the kidney, liver, and heart. Most of the patients with COVID-19 have mild symptoms, but 5% of cases are admitted to an intensive care unit (ICU) for severe symptoms, including multi-organ failure and septic shock. Excessive immune responses play an essential role in sepsis development and are associated with worse prognosis in COVID-19 patients. Consequently, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Next, protein tyrosine kinase-binding protein (TYROBP) combined with killer-cell activating receptor-associated protein (KARAP) to form an adapter that is involved in a broad range of biological functions, such as anti-viral and anti-tumor activities [ 41 ], and displayed inflammatory reactions [ 42 ]. Sialic acid-binding Ig-like lectin 10 (SIGLEG10) expressed a large amount in B1 cells, which controls inflammation by producing interleukin-10 (IL-10), interleukin-35 (IL-35), and granulocyte-macrophage colony-stimulating factor (GM-CFS) [ 43 ]. Taken together, we found that our gene index interacts with various proteins that play important functions in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Next, protein tyrosine kinase-binding protein (TYROBP) combined with killer-cell activating receptor-associated protein (KARAP) to form an adapter that is involved in a broad range of biological functions, such as anti-viral and anti-tumor activities [ 41 ], and displayed inflammatory reactions [ 42 ]. Sialic acid-binding Ig-like lectin 10 (SIGLEG10) expressed a large amount in B1 cells, which controls inflammation by producing interleukin-10 (IL-10), interleukin-35 (IL-35), and granulocyte-macrophage colony-stimulating factor (GM-CFS) [ 43 ]. Taken together, we found that our gene index interacts with various proteins that play important functions in immunity.…”
Section: Discussionmentioning
confidence: 99%